PENGEMBANGAN E-BOOK BERBANTUAN HEYZINE PADA MATERI INDONESIAKU KAYA ALAMNYA UNTUK MENINGKATKAN BERPIKIR KREATIF - Silma Hani; Didit Ardianto; Elly Sukmanasa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The research employed the Research and Development (R&D) method using theADDIE model, which consists of the stages: Analysis, Design, Development,Implementation, and Evaluation. The validation results indicated that the feasibilityratings were 89.2% from the material expert, 91.6% from the media expert, and88.8% from the language expert, all classified as "very feasible".Studentresponses to the e-book reached 94.2%, and teacher responses reached 96.4%,both classified as "very good".The products effectiveness was measured usingthe N-Gain test, which showed an average score of 0.67 (categorized as"moderately effective" and a t-test significance value of 0.000 < 0.05, indicating asignificant difference in the improvement of creative thinking skills between theexperimental and control classes. Thus, the Heyzine-assisted e-book is proven tobe highly feasible, positively received, and effective for use in IPAS learning toimprove students creative thinking skills.